The Implementation of Thematic Learning of an Ethnographic Study in Early Grade at Elementary School Ternate - Samsu Somadayo, Syahrir Ibnu, Kodrat Hi. Karim, Suhardi Abdullah (International Journal of Advanced Science and Technology, 2020)
The purposes of the research are 1) to know the thematic learning planning process, 2) to find out the thematic learning implementation, 3) to find out the results of thematic learning evaluation. This research is a qualitative descriptive study using an ethnographic research approach. Ethnographic research is research that involves learning activities about the world of people who have learned to see, hear, talk, think, and act in different ways. The population taken is the students of elementary schools in Ternate. The sampling technique in this study is the equal probability technique. This technique can be done by means of each population group can be selected a certain number of members to be included in the sample and each group member has the same probability to be included in the sample. Data collection procedures using questionnaires, interviews, (FGD) and documentation. The findings of the research are as follows (1) the results of thematic learning planning are 56.4%, (2) the results of the implementation of thematic learning are 55.41% and (3) the thematic learning assessment results are 51.35%. Thus, the average achievement of the implementation of thematic learning in Elementary School are 54, 38%.